Exploring student teachers' stressors in teaching practice in the COVID-19 era in Masvingo District, Zimbabwe - Marvelous Marenyenya (International Journal of Studies in Inclusive Education)
This study explores student teachers' resilience in teaching practice in the COVID-19 era in Masvingo District, Zimbabwe. More specifically, the study was intended to gain insights into the significant teaching practice COVID-19-induced teaching practice stressors. This research study contributes new knowledge to the ongoing discourses about student teachers' resilience in teaching practice in the COVID-19 era. To explore student teachers' resilience on teaching practice in COVID-19 era, the study employed a qualitative social constructivist approach through a phenomenological research design. Data were generated through focus group discussions and in-depth semi-structured interviews. One teachers' college was conveniently sampled, and twenty-one student teachers and six student teachers' mentors were purposively sampled from three primary schools in Masvingo District, Zimbabwe. Data were analysed using Interpretive Phenomenological Analysis. The thematic findings revealed that student teachers teaching practice in the COVID-19 era are subjected to teaching practice stressors induced by the COVID-19 pandemic, such as fear of contracting the COVID-19 virus, illness, isolation, stigmatization and death, anxiety, uncertainty, hopelessness, economic hardships, prolonged teaching practice period, school closures, transference of face-to-face teaching to online learning. Finally, thematic results revealed that the capacity for resilience can be developed during initial teacher preparation, so the study recommends that the teacher education curriculum include a module on resilience.